Controls on morphology of catchment-fan systems in the northwest margin of the Junggar Basin, northwest China - Zixiao Peng; Jianhua Qu; Zhijie Zhang; En Xie; Hongying Zhou; Li Wan; Dawei Cheng; Shunli Li; Xinghe Yu (Journal of Asian Earth Sciences, 2026)

Integrated scRNA-seq and bulk transcriptomics identify an amino acid metabolism-associated prognostic signature and highlight FUS as a potential driver in prostate cancer progression - Jiangbei Yuan; Dawei Shen; Zixiang Pan; Fei Lv; Yue Zhao; Wei Zheng; Qiaoqiao Yin; LanJie Wu; Jianli Yu; Cheng’an Xu; Qiang He; Hongying Pan (Functional & Integrative Genomics, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Single-nucleus atlas of porcine longissimus dorsi development reveals breed-specific myofiber maturation and stromal remodeling - Jingru Nie; Wei Cheng; Zhu Tao; Xinxing Dong; Dawei Yan; Bo Zhang; Hao Zhang (Food Research International, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Early-stage scour resistance and mechanisms of marine dredged clay-based cementitious slurry - Hao Meng; Dawei Guan; Liang Cheng; Tiago Fazeres-Ferradosa; Jisheng Zhang; Jinhai Zheng (Ocean Engineering, 2026)

The potential sources of sulfate and its effect on carbonates weathering in karst spring area, North China - Xiaojuan Qiao; Xinyu Chai; Yu Cheng; Dawei Wang; Wenjin Yu; Chunlei Tang (Journal of Hydrology, 2026)

Life cycle assessment of nickel laterite refining to battery materials intermediates in Indonesia: A case study - Ni Luh Dila Wahyu Kinanti; Kaihua Xu; Zebang Hu; Qiongwen Cheng; Dawei Yu (Hydrometallurgy, 2026)

Explainable artificial intelligence identifies key meteorological drivers of extreme precipitation in the Asian Monsoon Region - Yuan Tian; Yang Zhao; Jianping Li; Cheng Shen; Yazhou Zhang; Dawei Wen; Xin Qi; Yuan Liu; Dandan Chen (Atmospheric Research, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Characteristics of needle-to-plate discharge driven by combined DC and nanosecond pulse voltages and its nitrogen fixation performance - Ruihao Li; Zhiyu Li; Jialin Liu; Lanlan Nie; He Cheng; Dawei Liu; Xinpei Lu (Journal of Environmental Chemical Engineering, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Sedimentary response to Jurassic intracontinental orogenic process in Qinling Orogenic Belt: New insights from detrital zircon geochronology and heavy minerals in the Northeastern Sichuan Basin, SW China - Wenbin Tang; Shuaiwei Zhang; Dawei Cheng; Georgia Pe-Piper; Zhijie Zhang; Haitao Hong; Kai Yu; Mingcai Hou; Anqing Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Cleavage of Beclin 1 by metacaspase 1 activates antiviral autophagy in plants - Rujian Hu; Qinglin Pi; Meng Yang; Wen Song; Zhihao Jiang; Chenchen Zhong; Huanxi Han; Cheng-Gui Han; Yongliang Zhang; Dawei Li (Molecular Plant, 2026)

Multi-omics profiling delineates reheating-modality-driven flavor divergence in Yuxiang shredded pork - Xuan Wang; Shaoran Shi; Xiaomeng Wu; Shuang Bi; Fan Yang; Xiuli Du; Youyou Cheng; Jingguang Li; Yunfeng Zhao; Dawei Chen (Food Chemistry, 2025)

Findings in pedestrian route choice experiments: Tradeoff and hypothetical bias - Cheng-Jie Jin; Jiaxin Li; Chenyang Wu; Xiaoxuan Xiu; Dawei Li (Travel Behaviour and Society, 2025)

Impact load capacity assessment of cargo containment system considering various loading area and duration characteristics - Gao Dawei; Li Cheng; Shi Guijie (Ocean Engineering, 2025)

Capillarity effect on groundwater dynamics during periodic forcing - Dawei Cheng; Hongbin Zhan; Xi Chen; Shengke Yang; Dongyong Sun; Xiuyu Liang (Journal of Hydrology, 2025)

Terrestrosin D inhibits invasion and induces apoptosis through inhibition of STAT3 in anaplastic thyroid carcinoma - Honglai Zhang; Dawei Sun; Peijie Lei; Jingjing Cheng (Molecular & Cellular Toxicology, 2025)

Angle-resolved magneto-chiral anisotropy in a non-centrosymmetric atomic layer superlattice - Long Cheng; Mingrui Bao; Xue Zhang; Jingxian Zhang; Qun Yang; Qiang Li; Hui Cao; Dawei Qiu; Hui Li; Guanglei Cheng; Hua Zhou; Jian-Min Zuo; et al. (Science Bulletin, 2025)

The diversity and disparity of mineral elements in global kiwifruits - Dawei LI; Yan Min; Chang Cheng; Xiaoying Liu; Xiaodong Xie; Gudeta Chalchisa; Cheng Peng; Quan Jiang; Naidong Xiao; Jianbo Cai; Caihong Zhong (Food Research International, 2025)

Experimental study of dam-break-like tsunami loads on vertical structures with overhanging horizontal slabs: Slab with air chamber - Chen Peng; Cheng Chen; N.A.K. Nandasena; Xin Deng; Feng Cai; Dawei Guan (Ocean Engineering, 2024)

A novel strategy for detoxification of deoxynivalenol via modification of both toxic groups - Bingqian Hou; Yongchang Xu; Dawei Wang; Chunmei Dong; Fangfang Yan; Xinxin Cheng; Silong Sun; Cunyao Bo; Zhangwei Liu; Yao Qin; Hongwei Wang; Lingrang Kong (Food Chemistry, 2024)

A robust 3D nanostructured composite polymer electrolyte with novel dual-ion channels toward solid-state sodium metal batteries - Yunlong Cui; Pengyu Zhang; Yuan Tian; Cheng Wang; Su Wang; Yan Zhang; Xixi Shi; Yue Ma; Dawei Song; Hongzhou Zhang; Kai Liu; Na Zhang; et al. (Chemical Engineering Journal, 2024)

Enhancing typhoon wave hindcasting with random forests and BP neural networks in the SWAN model - Cheng Chen; Hongkun Lin; Dawei Guan; Feng Cai; Qiaoyi Wang; Qingchun Liu (Frontiers in Marine Science, 2024)
Forecasting typhoon waves during typhoons is crucial. In this paper, the numerical wave model SWAN was enhanced through integration with two machine learning methods: the Back Propagation Neural Network and Random Forest. This integration facilitated the development of two distinct models, namely SWAN-BP and SWAN-Tree. Through correlation analysis, key input features were identified for the machine learning models. The forecasts from the SWAN model were subsequently utilized as inputs to enhance further wave prediction. These hybrid models were validated using data from Typhoon Doksuri (2023) and Typhoon Nesat (2017). The results indicated significant improvements in predicting typhoon-induced wave heights with both the SWAN-BP and SWAN-Tree models compared to the original SWAN model. Specifically, the SWAN-BP model demonstrated a 33% improvement in accuracy for the Typhoon Doksuri, whereas the SWAN-Tree model exhibited a 24% improvement. For Typhoon Nesat, the accuracy improvements were 23% for the SWAN-BP model and 21% for the SWAN-Tree model. These findings demonstrate that integrating wave numerical models with machine learning techniques can significantly enhance the predictive accuracy of numerical models. This approach offers a cost-effective means to improve the existing wave forecasting database. Traditionally, the direct use of meteorological and oceanographic data for typhoon wave prediction might be compromised by biases inherent in the numerical wave models. However, the SWAN-BP and SWAN-Tree models effectively reduce these biases, thereby providing more accurate and robust predictions. In conclusion, this paper enhances the predictive accuracy of the SWAN model and establishes a crucial foundation for more precise typhoon wave forecasting through the application of machine learning techniques.

Numerical Simulation of Flow Field around Jacket Foundations on Flat-Bed and Equilibrium Scour Bathymetry - Dawei Guan; Yinuo Chu; Cheng Chen; Jingang Liu; Zishun Yao (Journal of Marine Science and Engineering, 2024)
In recent years, jacket foundations have been increasingly employed in offshore wind farms. Their complex design comprising piles and trusses poses challenges for conducting comprehensive flow field measurements using physical experiments. Consequently, the influence of the flow field on local scour around these foundations remains unclear. Therefore, numerical simulation methods are essential to depict the surrounding flow characteristics. This study utilizes large eddy simulation (LES) turbulence models within OpenFOAM to simulate the flow field around jacket foundations on flat-bed and equilibrium scour bathymetry. A flume experiment was conducted for numerical model establishment and validation. The close agreement between experimental and numerical results indicates that the LES model accurately reflects the flow patterns around the jacket foundation. Time-averaged and instantaneous flow characteristics, average kinetic energy (AKE), turbulence structure, and bed shear stress were analyzed. The results indicate that flow intensity is reduced due to the shielding effect and energy dissipation by the truss structure of the jacket foundation. Furthermore, the AKE of the flow upstream of the rear piles decreases by 18.9% in the flat-bed state and 28.0% in the equilibrium state, indicating more energy dissipation and less scour at the rear piles in the equilibrium state. The research findings offer valuable insights into the design and scour protection strategies for jacket foundations.

Water accumulation unrelated to ice segregation near the freezing front during soil freezing: Implications for frost heave in high-speed railway embankments and ground ice formation - Lianhai Zhang; Yajun Shi; Chengsong Yang; Wei Ma; Dawei Han; Fei Shang; Cheng Chen; Yuzhong Yang (CATENA, 2024)

Development of porous materials via protein/polysaccharides/polyphenols nanoparticles stabilized Pickering high internal phase emulsions for adsorption of Pb2+ and Cu2+ ions - Cheng Wang; Mian Wei; Huipeng Zhu; Lu Wang; Song Ni; Xiaoyu Li; Dawei Gao (Food Chemistry, 2024)

Routes with roots: Pedestrian route choices and sense of place of an urban university community - Ho-Yin Chan; Dawei Cheng; Anthony Chen (Journal of Transport Geography, 2024)

VOC and IVOC emission features and inventory of motorcycles in China - Zhining Zhang; Hanyang Man; Junchao Zhao; Wendong Huang; Cheng Huang; Shengao Jing; Zhenyu Luo; Xinyue Zhao; Dawei Chen; Kebin He; Huan Liu (Journal of Hazardous Materials, 2024)

Fhb7-GST catalyzed glutathionylation effectively detoxifies the trichothecene family - Bingqian Hou; Dawei Wang; Fangfang Yan; Xinxin Cheng; Yongchang Xu; Xuepeng Xi; Wenyang Ge; Silong Sun; Peisen Su; Lanfei Zhao; Zhongfan Lyu; Yongchao Hao; et al. (Food Chemistry, 2024)

Hydrodynamics drives shifts in phytoplankton community composition and carbon-to-chlorophyll a ratio in the northern South China Sea - Dawei Chen; Zhen Shi; Ruihuan Li; Xiangfu Li; Yuanyue Cheng; Jie Xu (Frontiers in Marine Science, 2023)
Phytoplankton play significant roles in the carbon cycle in oceans. Phytoplankton biomass and community composition are often mediated by ocean hydrodynamics. It is vital to quantify the phytoplankton carbon content and carbon:Chlorophyll a (C:Chl a ) ratio and to better understand the link between hydrodynamics and phytoplankton communities in marine environments, which are important parameters in marine biogeochemical models. Environmental variables, phytoplankton community composition, abundance, particulate organic carbon, and Chl a were determined in summer in the northern South China Sea (SCS), which was influenced by the Pearl River discharge, upwelling, and anticyclonic eddy, to examine the links between hydrodynamics, phytoplankton community, and C:Chl a ratio. Our results showed that the spatial variabilities in phytoplankton community composition, and carbon content, and C:Chl a ratio were driven by hydrodynamics. Nutrient enrichment favored the growth of diatoms, especially small chain-forming diatoms at the Pearl River Estuary stations. From inshore to offshore, the dominant phytoplankton shifted from small-chain diatoms to large diatoms and dinoflagellates, increasing phytoplankton biodiversity from inshore to offshore. Weak upwelling caused an increase in Synechococcus abundance, while an anticyclonic eddy resulted in a high abundance of Prochlorococcus and Trichodesmium spp. in the present study. We found that the relationship between phytoplankton carbon content and the logarithm of Chl a concentration fit an exponential curve. The C:Chl a ratio increased from 72.7 g g −1 at Pearl River Estuary stations, to 101 g g −1 at Pearl River discharge dilution stations and to 131 g g −1 at SCS surface stations due to shifts in phytoplankton community composition. The low C:Chl a ratio was attributed to the high abundance of diatoms in the Pearl River plume-impacted area, whereas a high C:Chl a ratio was related to the dominance of cyanobacteria at SCS surface stations. Our findings provide insights into quantifying phytoplankton carbon content and understanding the links between hydrodynamics, phytoplankton community composition, carbon content, and C:Chl a ratio in oceans.

Aging behavior and mechanism of polyvinylidene fluoride membrane by intensified UV irradiation and NaOCl: A comparative study - Xiang Zheng; Danyang Dai; Helin Hua; Dawei Yu; Rong Cheng; Libing Zheng (Process Safety and Environmental Protection, 2023)

Highly flexible multilayer MXene hollow carbon nanofibers confined with Fe3C particles for high-performance lithium-ion batteries - Xiaohong Lu; Jinbing Cheng; Dawei Zhou; Yichong Chen; Hao Jiang; Yang Lu; Deyang Zhang; Dezhi Kong; Paul K. Chu; Hui Ying Yang; Yongsong Luo (Chemical Engineering Journal, 2023)

Social support and relapse tendency in Chinese women experiencing heroin addiction: A moderated mediation model of active coping strategies and openness to experience - Dawei Huang; Li Liu; Jiangzhong Liu; Gang Cheng (The Social Science Journal, 2023)

Shaking table test on underground structure-soil-aboveground structure interaction - Ye Cheng; Danguang Pan; Qingjun Chen; Ying Huang; Dawei Zhang (Tunnelling and Underground Space Technology, 2023)

Increased ascorbic acid synthesis by overexpression of AcGGP3 ameliorates copper toxicity in kiwifruit - Xiaoying Liu; Chang Cheng; Yan Min; Xiaodong Xie; Abu Naim Md. Muzahid; Haiyan Lv; Hua Tian; Congxiao Zhang; Can Ye; Shifeng Cao; Peng Chen; Caihong Zhong; et al. (Journal of Hazardous Materials, 2023)

Guest molecule optimum aggregation hypothesis and optimal concentrations for energy storage from the perspective of hydrate phase change-induced liquid layer - Fan Wang; Yuan Lv; Xinran Xia; Lizhong Yang; Dawei Guan; Chuanxiao Cheng; Wenfeng Hu; Lunxiang Zhang; Alessandro Romagnoli; Jiafei Zhao; Yongchen Song (Journal of Cleaner Production, 2023)

Parametric analysis and numerical optimisation of spinach root vibration shovel cutting using discrete element method - Liangliang Zou; Dawei Yan; Ziru Niu; Jin Yuan; Hao Cheng; Hao Zheng (Computers and Electronics in Agriculture, 2023)

Characteristic of regional groundwater flow system: case modeling study in Longzici karst spring area, North China - Xiaojuan Qiao; Yu Cheng; Dawei Wang (Acta Geophysica, 2023)

Influences of Two Plant Growth Regulators on the Fruit Quality of the ‘Crimson Seedless’ Grapes - Lan Li; Weijiao Yan; Huidong Yao; Hui Li; Xizhi Guo; Dawei Cheng; Junli Sun; Jinyong Chen (Journal of Plant Growth Regulation, 2023)

Construction of porous materials from Pickering high internal-phase emulsions stabilized by zein-Hohenbuehelia serotina polysaccharides nanoparticles and their adsortion performances - Cheng Wang; Lu Wang; Siying An; Qianyu Jiang; Dawei Gao; Xiaoyu Li (Food Hydrocolloids, 2023)

Selective corticocortical connectivity suppression during propofol-induced anesthesia in healthy volunteers - Haidong Wang; Yun Zhang; Huanhuan Cheng; Fei Yan; Dawei Song; Qiang Wang; Suping Cai; Yubo Wang; Liyu Huang (Cognitive Neurodynamics, 2022)

Paleo-Environment Reconstruction of the Middle Permian Lucaogou Formation, Southeastern Junggar Basin, NW China: Implications for the Mechanism of Organic Matter Enrichment in Ancient Lake - Dawei Cheng; Chuanmin Zhou; Zhijie Zhang; Xuanjun Yuan; Yinhe Liu; Xingyu Chen (Journal of Earth Science, 2022)

Bioaugmentation mitigates ammonia and hydrogen sulfide emissions during the mixture compost of dewatered sewage sludge and reed straw - Qingli Cheng; Longlong Zhang; Dawei Wang; Bochao Niu (Environmental Science and Pollution Research, 2021)

The Effect of Pre-heating Treatment and Water–Cement Ratio on the Shearing Behavior and Permeability of Granite–Cement Interface Samples - Fan Zhang; Tanzhuo Cheng; Zhenzhen Zhu; Dawei Hu; Jianfu Shao (Rock Mechanics and Rock Engineering, 2021)

Rapid assessment of landslide risk level based on deep learning - Fei Tan; Jin Yu; Yu-Yong Jiao; Dawei Lin; Jiahe Lv; Yi Cheng (Arabian Journal of Geosciences, 2021)

Machine learning for predicting discharge fluctuation of a karst spring in North China - Shu Cheng; Xiaojuan Qiao; Yaolin Shi; Dawei Wang (Acta Geophysica, 2021)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Genetic characteristics of the P1 coding region of Coxsackievirus A16 associated with hand, foot, and mouth disease in China - Li Xu; Dawei Cui; Lei Wang; Jun Cheng; Changgui Sun; Lanjuan Li; Hongcui Cao (Molecular Biology Reports, 2018)

Study of a full-wave equation-based seismic illumination analysis - Wei Liu; Cheng Yin; Dawei Li; Da Peng; Shulin Pan (Arabian Journal of Geosciences, 2017)

Effects of returning NF concentrate on the MBR-NF process treating antibiotic production wastewater - Kun Li; Yutao Cheng; Jianxing Wang; Junya Zhang; Jibao Liu; Dawei Yu; Mingyue Li; Yuansong Wei (Environmental Science and Pollution Research, 2016)

Folate and TAT Peptide Co-Modified Liposomes Exhibit Receptor-Dependent Highly Efficient Intracellular Transport of Payload In Vitro and In Vivo - Yaqin Zhu; Liang Cheng; Lifang Cheng; Fazhen Huang; Qing Hu; Ling Li; Chenmin Tian; Lin Wei; Dawei Chen (Pharmaceutical Research, 2014)

Expression of SGTA correlates with neuronal apoptosis and reactive gliosis after spinal cord injury - Minhao Chen; Xiaopeng Xia; Xinhui Zhu; Jianhua Cao; Dawei Xu; Yingjie Ni; Yang Liu; Shixian Yan; Xinghai Cheng; Yonghua Liu; Youhua Wang (Cell and Tissue Research, 2014)

Association of polymorphisms in folate metabolic genes and prostate cancer risk: a case-control study in a Chinese population - Dawei Cai; Lin Ning; Chunyu Pan; Xuefeng Liu; Renge Bu; Xiaonan Chen; Kefeng Wang; Yang Cheng; Bin Wu (Journal of Genetics, 2010)